Emerging Innovations and Trends in Academic Libraries of Pakistan in the 21st Century - Gulzar Ahmed Lakho; Shazia Gul Memon; Nazia Iqbal; Fajar Janat (Inverge Journal of Social Sciences, 2025)
This research paper explores the new technology, emerging trends and challenges that academic libraries in Pakistan tend to encounter in the 21st century. It seeks to evaluate the ways in which the digital transformation is transforming library operations, user services as well as professional functions and also determine where it is heading to in terms of sustainable development. A quantitative descriptive study design was adopted with a structured questionnaire to be given to 200 library professionals in the public and the private universities in Pakistan. The data were interpreted through descriptive statistics (frequency and percent) to generalize the perceptions of the respondents on technological adoption, service innovations and institutional challenges. The findings show that there has been a drastic change towards digitalization as majority of libraries have embraced automation in cataloguing, OPAC and cloud based services. Digital literacy training, provision of virtual reference services and utilization of social media in engaging libraries are also emerging practices that have been adopted by libraries. Nevertheless, certain obstacles like lack of sufficient funding, ineffective ICT, ineffective infrastructure, and institutional support remain in the way. There was a great deal of optimism about the future, which included professional development, collaboration, and national policy support as respondents thought that innovation can continue to flourish. The results indicate that there is a requirement to invest in ICT infrastructure strategically, continuous professional training, and development of policy frameworks to facilitate equitable technological development within academic institutions. Innovation and quality of service can be even improved through strengthening institutional support and collaboration. The given research offers the detailed data-driven information on the technological revolution in the field of the Pakistani academic libraries, which is acute considering the lack of information about the situation on the ground in Pakistan and in the context of the digital era, in general. References Ahmed, S., Sheikh, A., & Akram, M. (2018). Implementing knowledge management in university libraries of Punjab, Pakistan. Information Discovery and Delivery, 46(2), 83–94. https://doi.org/10.1108/IDD-02-2018-0004 Ali Khan, T. (2023). Examining the impact of university libraries in facilitating foreign language learning in Pakistan. International Journal of Librarianship and Information Science, 5(1), 10–18. Arif, M., & Mahmood, K. (2012). The changing role of librarians in the digital world: Adoption of Web 2.0 technologies by Pakistani librarians. The Electronic Library, 30(4), 469–479. https://doi.org/10.1108/02640471211247040 Ashiq, M., Rehman, S. U., & Mujtaba, G. (2021). Future challenges and emerging role of academic libraries in Pakistan: A phenomenology approach. Information Development, 37(1), 158–173. https://doi.org/10.1177/0266666920917113 Asif, M., & Asghar, R. J. (2025). Managerial accounting as a driver of financial performance and sustainability in small and medium enterprises in Pakistan. Center for Management Science Research, 3(7), 150-163. https://doi.org/10.5281/zenodo.17596478 Asif, M., Shah, H., & Asim, H. A. H. (2025). Cybersecurity and audit resilience in digital finance: Global insights and the Pakistani context. Journal of Asian Development Studies, 14(3), 560-573. https://doi.org/10.62345/jads.2025.14.3.47 Awais, S., & Ameen, K. (2019). The current innovation status of university libraries in Pakistan. Library Management, 40(3/4), 178–190. https://doi.org/10.1108/LM-11-2018-0096 Afzal, M., Arshad, N., & Shaheen, A. (2025). ChatGPT and the future of academic writing: Enhancing productivity and creativity. Journal of Engineering and Computational Intelligence Review, 3(1), 1–11. Baber, M., Islam, K., Ullah, A., & Ullah, W. (2024). Libraries in the age of intelligent information: AI-driven solutions. International Journal of Applied and Scientific Research, 2(1), 153–176. Bashir, F. (2020). Ambassador of lifelong learning/public libraries in multicultural society: The case of Pakistan. Türk Kütüphaneciliği, 34(3), 548–558. Batool, S. H., Rehman, A. U., & Sulehri, I. (2022). The current situation of information literacy education and curriculum design in Pakistan: A discovery using Delphi method. Library Hi Tech, 40(6), 1705–1720. https://doi.org/10.1108/LHT-07-2021-0168 Bibi, T. (2024). Academic advancement: Libraries' integral support for research in public sector universities of Khyber Pakhtunkhwa, Pakistan. Journal of Computing & Biomedical Informatics, 7(1), 559–570. Butt, R., Siddiqui, H., Soomro, R. A., & Asad, M. M. (2020). Integration of Industrial Revolution 4.0 and IOTs in academia: A state-of-the-art review on the concept of Education 4.0 in Pakistan. Interactive Technology and Smart Education, 17(4), 337–354. https://doi.org/10.1108/ITSE-03-2020-0032 Gul, S., & Bano, S. (2019). Smart libraries: An emerging and innovative technological habitat of 21st century. The Electronic Library, 37(5), 764–783. https://doi.org/10.1108/EL-09-2018-0171 Hanif, S., Shah, S. A. A., Rehman, A. U., & Hassan, S. (2024). Changing role of libraries and librarians in the new technological era: An evaluative study of university libraries of Islamabad. Bulletin of Business and Economics (BBE), 13(2), 448–454. Hussain, A. (2020). Industrial revolution 4.0: Implication to libraries and librarians. Library Hi Tech News, 37(1), 1–5. https://doi.org/10.1108/LHTN-01-2020-0006 Iqbal, Q., Akbar, T., Zia, M., Ahmed, R., & Cheema, A. M. (2024). Transforming library leadership: Redefining leadership in the digital era and its impact on innovative work behavior in Pakistan. Journal of Information Management and Practices, 4(2). Islam, K., Shamshad, A., & Usman, M. (2025). Adoption potential of artificial intelligence and machine learning in Islamabad’s academic libraries. Journal of Engineering and Computational Intelligence Review, 3(1), 12–24. Khalid, A., Malik, G. F., & Mahmood, K. (2021). Sustainable development challenges in libraries: A systematic literature review (2000–2020). The Journal of Academic Librarianship, 47(3), 102347. https://doi.org/10.1016/j.acalib.2021.102347 Khan, M. I., Jan, R., Hussain, M., & Bahadar, M. (2024). Perception, competencies, and potential challenges towards big data management among the university libraries of Khyber Pakhtunkhwa. Journal of Regional Studies Review, 3(1), 21–28. Kiran, N., Aziz, T., & Lashari, A. A. (2024). Academic libraries emerging trends in 21st century: A systematic review. Pakistan Social Sciences Review, 8(1), 270–281. Malik, A., & Ameen, K. (2021). The employment landscape and LIS education in Pakistan: Challenges and prospects. Global Knowledge, Memory and Communication, 70(1/2), 79–93. https://doi.org/10.1108/GKMC-02-2021-0036 Rafi, M., JianMing, Z., & Ahmad, K. (2019). Technology integration for students’ information and digital literacy education in academic libraries. Information Discovery and Delivery, 47(4), 203–217. https://doi.org/10.1108/IDD-08-2018-0037 Shah, S. H., Shah, N. U., & Jbeen, A. (2024). Exploration of LIS professionals efforts in Pakistan towards the improvements of technological competencies in 21st century. Global Knowledge, Memory and Communication, 73(4/5), 596–613. Soroya, S. H., & Ameen, K. (2020). Millennials’ reading behavior in the digital age: A case study of Pakistani university students. Journal of Library Administration, 60(5), 559–577. https://doi.org/10.1080/01930826.2020.1772513 Ullah, A., & Usman, M. (2023). Role of Libraries in Ensuring Quality Education at Higher Education Institutions: A Perspective of Pakistan. Inverge Journal of Social Sciences, 2(4), 13–22. https://doi.org/10.63544/ijss.v2i4.57 Zahra, M., Hanif, S., & Shah, S. A. A. (2024). Current technological trends used in libraries: A study of public sector universities of Khyber Pakhtunkhwa, Pakistan. Journal of Development and Social Sciences, 5(3), 87–99.